Cutaneous horn developing over a verrucous carcinoma: a rare entity with an unusual presentation - Gupta, Rajesh; Lavania, Prashant; Bansal, Vikas Kumar; Agarwal, Neelabh; Singh, Aradhana (International Surgery Journal, 2016)
Cutaneous horn (cornu cutaneum) is a very rare lesion resembling the horn of an animal. It consists of a projectile, conical, dense, hyperkeratotic nodule. The horn is frequently conical, made of stratum corneum. Diagnosis is easily made clinically and can be confirmed by histopathology. We report a case of 65 year old female, who had a cutaneous horn for over 5 months, which turned out to be growing over a verrucous carcinoma.